1982
DOI: 10.1007/bf00156118
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the magnetic structure of the inner heliosphere by means of a non-spherical source surface

Abstract: LABORATORY OPERATIONSThe Laboratory OperatIons of The Aerospace CorporatIon lS conductmg expenmental and theoretIcal mvestIgahons necessary for the evaluatIon and apphcatIon of sClentIftc advances to new mlhtary concepts and systems Versahhty and flexlblhty have been developed to a hlgh degree by the laboratory personnelln deahng With the many problems encountered ln the nahon's rapldly developlng space and mlsslle systems Experhse m the latest sClenhflC developments lS vltal to the accomphshment of tasks rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 29 publications
1
35
1
Order By: Relevance
“…For now this is just a working hypothesis to be tested against future Ulysses data. However, Levine et al (1982) found that a similarly (although parametrically more cumbersome) intermediate shape between k 0 and k 1 could account quite well not only for the MHD field configuration obtained by Pneuman and Kopp (1971a,b) in the dipolar test case, but also for a more complicated coronal and interplanetary B-field configuration encountered not far from solar maximum.…”
Section: Source Surfacesupporting
confidence: 66%
See 3 more Smart Citations
“…For now this is just a working hypothesis to be tested against future Ulysses data. However, Levine et al (1982) found that a similarly (although parametrically more cumbersome) intermediate shape between k 0 and k 1 could account quite well not only for the MHD field configuration obtained by Pneuman and Kopp (1971a,b) in the dipolar test case, but also for a more complicated coronal and interplanetary B-field configuration encountered not far from solar maximum.…”
Section: Source Surfacesupporting
confidence: 66%
“…The goal in choosing a nonspherical source surface is to arrange for the region(s) of minimal source-surface curvature to straddle the inner edge(s) of any heliospheric current sheet(s). The choice of a surface of constantF as source surface shows some promise in this regard (Schulz et al, 1978;Levine et al, 1982; and in the present work) but is not guaranteed to achieve the desired configuration. However, the purpose is likely to be defeated altogether (especially near solar maximum, whenB is quite complicated and multiple heliospheric current sheets are possible) if some fixed shape is assigned to the source surface, regardless of the form ofB.…”
Section: Summary and Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…F 1 is generally taken to be a sphere of radius r~ (r~ being a free parameter, sometimes taken infinite to further simplify the model) (Semel, 1967;Newkirk et al, 1968;Schatten et aL, 1969;Altschuler and Newkirk, 1969;Adams and Pneuman, 1976;Riesebieter and Neubauer, 1979;Sakurai, 1982;Bogdan, 1986). However, new models have been recently proposed in which F1 has a more complicated shape, determined by using an extra physical criterion (Schulz etaL, 1978;Levine et aL, 1982). In all those simple 'potential models', what is just required in principle for computing B is, F1 being fixed, the value at all the points of Fo of the component B l of B/Fo along some direction l'(r).…”
Section: Introductionmentioning
confidence: 99%